POLR3-related leukodystrophy caused by biallelic POLR3A and 1C pathogenic variants: a single-center experience - Liu, Jing; Niu, Yue; Qin, Jiong; Yang, Zhixian (Frontiers in Neurology, 2024)
Objectives: To investigate the clinical, radiological and genetic features of POLR3-related leukodystrophy caused by mutations in POLR3A or POLR1C.Methods: Fourteen Chinese patients with POLR3-related leukodystrophy were enrolled in this cross-sectional observational study. We evaluated the clinical manifestations of the patients via brain MRI and genetic tests.Results: Thirteen patients had biallelic variants in POLR3A (92.9%), and one had biallelic variants in POLR1C (7.1%). The median age at disease onset was nine months. A total of 85.7% of patients presented with motor delay, abnormal gait and intelligence disability in the first two years of life. Intelligence disability varied from mild (only with trouble concentrating) to very severe (with no smiling or laughing or never able to speak since birth). Short stature was observed in all patients, and retarded dentition was observed in 64.3%. Three of the 14 patients had myopia.Hypomyelination was invariably present in all patients, whereas in 6/14 participants, myelination of the basal ganglia was preserved. All the mutations were compound heterozygous and included missense variants (n=25), deletion variants (n=1), and splice site variants (n=2). A total of 78.6% of patients with POLR3A were identified as carrying the c.1771-6C > G variant or the c.1771-7C > G variant.: The phenotypic diversity of POLR3-HLD associated with pathogenic variants is broad, ranging from mild to very severe for neurological and nonneurological symptoms. Most patients presented symptoms in the first two years of life. The c.1771-6C > G or c.1771-7C > G variant is the most frequent mutation site in POLR3A in Chinese individuals.